Relationship between depression and quality of life among vitiligo patients: A self-assessment questionnaire-based study - Narumol Silpa-Archa (2020)
© 2020 Silpa-archa et al. Background: Vitiligo is a common chronic autoimmune disease that is characterized by progressive loss of skin color due to melanocyte destruction. In addition to the physical effects of vitiligo, this condition exerts adverse psychological effects and causes social stigmatization. Earlier studies reported that individuals with vitiligo suffer from poor quality of life (QoL), but data about the QoL of Thai vitiligo patients is scarce. Objective: This study aimed to investigate the QoL and prevalence of depression in Thai vitiligo patients, association between QoL and depression, and factors associated with QoL and depression among Thai people with vitiligo. Methods: This cross-sectional self-assessment questionnaire-based study was conducted at the phototherapy and vitiligo clinics of the Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University (Bangkok, Thailand). QoL was assessed using the Dermatology Life Quality Index (DLQI) questionnaire, and depression was evaluated via the Patient Health Questionnaire (PHQ-9). Results: Among the 104 vitiligo patients that were recruited, the mean DLQI score was 7.46, and the prevalence of depression (PHQ-9 ≥9) was 13.5%. Factors significantly associated with a higher mean DLQI score were skin phototype IV compared to phototype III, active disease, new lesions within the last three months, lesions involving upper extremities, and PHQ-9 ≥9 (p<0.05). Moderate correlation was found between DLQI score and PHQ-9 score (Pearson’s correlation coefficient: 0.524, p<0.001). Factors significantly associated with depression were working status and developing new lesions within the last three months (p<0.05). Patients with new lesions were 4.12 times more likely to be depressed than those without new lesions (OR: 4.12, 95%CI: 1.20–14.16; p=0.025). Conclusion: Developing new lesions, active disease, dark skin phototype (IV), and lesion on upper extremity had significant adverse effects on QoL. Vitiligo patients who were employed and who had new vitiligo lesions are significantly more likely to be depressed.